Living on next to nothing: tree seedlings can survive weeks with very low carbohydrate concentrations. Issue 1 (9th February 2018) - Weber, Raphael; Schwendener, Andrea; Schmid, Sandra; Lambert, Savoyane; Wiley, Erin; Landhäusser, Simon M.; Hartmann, Henrik; Hoch, Günter
Summary: The usage of nonstructural carbohydrates (NSCs) to indicate carbon (C) limitation in trees requires knowledge of the minimum tissue NSC concentrations at lethal C starvation, and the NSC dynamics during and after severe C limitation. We completely darkened and subsequently released seedlings of two deciduous and two evergreen temperate tree species for varying periods. NSCs were measured in all major organs, allowing assessment of whole‐seedling NSC balances. NSCs decreased fast in darkness, but seedlings survived species‐specific whole‐seedling starch concentrations as low as 0.4–0.8% per dry matter (DM), and sugar (sucrose, glucose and fructose) concentrations as low as 0.5–2.0% DM. After re‐illumination, the refilling of NSC pools began within 3 wk, while the resumption of growth was delayed or restricted. All seedlings had died after 12 wk of darkness, and starch and sugar concentrations in most tissues were lower than 1% DM. We conclude that under the applied conditions, tree seedlings can survive several weeks with very low NSC reserves probably also using alternative C sources like lipids, proteins or hemicelluloses; lethal C starvation cannot be assumed, if NSC concentrations are higher than the minimum concentrations found in surviving seedlings; and NSC reformation after re‐illumination occurs preferentially over growth.